2011
DOI: 10.1200/jco.2010.31.5721
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Conformal Hypofractionated Radiotherapy With Concurrent Gemcitabine in Muscle-Invasive Bladder Cancer

Abstract: Concurrent gemcitabine-based chemoradiotherapy (ie, GemX) produces a high response rate in MIBC and has durable local control and acceptable toxicity, which allows patients to preserve their own bladder. This treatment modality warrants additional investigation in a phase III setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(105 citation statements)
references
References 36 publications
3
98
0
4
Order By: Relevance
“…83 According to a phase II trial from the same group using weekly gemcitabine at 100 mg/m 2 with concurrent conformal radiotherapy at 52.5 Gy, the CR rate was 88% (44/50) and 5-year OS and CSS rates were 65% and 78%, respectively. 85 These results encourage phase III trials. In recent series of trimodality therapy (Table 1), systemic chemotherapy with gemcitabine and cisplatin (GC regimen), which showed equivalent efficacy and less toxicity than the MVAC regimen in metastatic bladder cancer patients, 86 was combined in neoadjuvant 23,25 or adjuvant settings.…”
Section: Intensification Of Concomitant or Adjuvant Chemotherapymentioning
confidence: 92%
“…83 According to a phase II trial from the same group using weekly gemcitabine at 100 mg/m 2 with concurrent conformal radiotherapy at 52.5 Gy, the CR rate was 88% (44/50) and 5-year OS and CSS rates were 65% and 78%, respectively. 85 These results encourage phase III trials. In recent series of trimodality therapy (Table 1), systemic chemotherapy with gemcitabine and cisplatin (GC regimen), which showed equivalent efficacy and less toxicity than the MVAC regimen in metastatic bladder cancer patients, 86 was combined in neoadjuvant 23,25 or adjuvant settings.…”
Section: Intensification Of Concomitant or Adjuvant Chemotherapymentioning
confidence: 92%
“…Choudhury et al [4] who reported OAS 75% at 3 years, Cheon et al [21] who reported 74% at 2 years and Lin et al [22] who reported 77% at 3 years. However, Donald et al [15] reported OAS at 3 years 83%, that mostly due to more aggressive protocol including adjuvant chemotherapy (cisplatin and 5 FU).…”
Section: Figure 2 Bladder Intact Survivalmentioning
confidence: 99%
“…Trimodality bladder-sparing approaches consisting of transurethral resection (TUR), chemotherapy and radiotherapy (RT) yield overall survival rates comparable with those of radical cystectomy series (50%-70% at 5 years), while preserving the native bladder in 40%-60% of muscle-invasive bladder cancer patients, contributing to an improvement in quality of life for such patients [3][4][5] .…”
mentioning
confidence: 99%
“…Although there are no prospective randomized trials of concurrent chemoradiation (CRT) versus cystectomy, the Medical Research Council (MRC) trial did show better outcomes with 3 cycles of CMV before radiation therapy or cystectomy (25). A phase II trial evaluating concurrent weekly gemcitabine with radiation in 50 patients with T2-3 disease showed good tolerability and a CR rate of 88%, 3-year cancer-specific survival of 82%, and OS of 75% (38). Bladder-sparing approaches focusing on tumor biology, such as radiation with p53-targeted agents or hypoxiamodifying agents, are under study.…”
Section: Bladder Preservation In Muscle-invasive Diseasementioning
confidence: 99%